Properties of a Subclass of Avakumović Functions and Their Generalized Inverses - Buldygin, V.V.; Klesov, O.I.; Steinebach, J.G. (Український математичний журнал, 2002)
We study properties of a subclass of ORV functions introduced by Avakumović and provide their applications for the strong law of large numbers for renewal processes.